Dietary selection of L’Hoest monkeys in Kalinzu forest reserve, southwestern Uganda - Tolo, C. U.; Baranga, J.; Rugunda, Grace Kagoro (African Journal of Ecology, 2017)
Reports on patterns of dietary selection of forest guenons tend to be general and often classify Cercopithecus l’hoesti as a frugivores–folivores species just like the other guenons, and to date there has been no systematic investigation into the inventory of the species’ food items in the remaining forest fragments to guide major conservation and management decisions. Here we report on the L’Hoest monkeys’ main food species and how the selection of these foods varies among different age groups of the troop in Kalinzu Forest, Uganda for a period of 12 months. Behavioural observations were determined using scan samples [Behaviour, 49 (1974) 227]. Two hypotheses were evaluated in this study. Results indicate that individuals of different age groups have the ability to select a variety of both plant and invertebrate food items in the vicinity to supplement their diets. There was no significant difference in dietary selection between different age groups of L’Hoest monkey for a particular food type (ANOVA: Column analysis, F3,84 = 1.541337, P = 0.209827). However, significant difference was realized in dietary selection of the different food types by a particular age group (ANOVA: F22,46 = 40.86429, P = 3.69 ・ 10)23). Selective predation pressure against the infants and juveniles by Stephanoaetus coronatus was believed to be one of the likely reasons why infants and juveniles least exposed themselves in the trees feeding on fruits of Musanga leo-errerae and Ficus spp. Invertebrate feeding was found to constitute high percentage (47.2%) of the species diet and plant materials comprised (52.8%) than previously reported in other study sites. These data provide potentially useful insight on the feeding ecology of the little studied C. l’hoesti and can provide baseline information on conservation of its food items in the remaining forests.
Keywords: Cercopithecus l’hoesti; dietary selection; Kalinzu forest